Adaptations to the stressful combination of serpentine soils and Mediterranean climate drive plant functional groups and trait richness - Hidalgo-Triana, Noelia; Pérez-Latorre, Andrés V.; Adomou, Aristide Cossi; Rudner, Michael; Thorne, James H. (Frontiers in Plant Science, 2023)
Plant functional traits (FTs) are important for understanding plant ecological strategies (e.g., drought avoidance), especially in the nutrient-poor soils of serpentine ecosystems. In the Mediterranean areas, such ecosystems are characterized by climatic factors (e.g., summer drought) that exert a filtering effect. In our study, we analyzed 24 species with varying serpentine affinity, from strictly serpentine plants to generalist plants, from two ultramafic shrublands in southern Spain, considering four FTs: plant height (H), leaf area (LA), specific leaf area (SLA), and stem specific density (SSD). Additionally, we also identified the species’ dominant strategies to avoid drought and those strategies’ relationship to serpentine affinity. We used principal component analysis to identify combinations of FTs, and cluster analysis to define Functional Groups (FGs). We defined eight FGs, which suggests that such Mediterranean serpentine shrublands are composed of species with wide-ranging of FTs. Indicator traits explained 67–72% of the variability based on four strategies: (1) lower H than in other Mediterranean ecosystems; (2) middling SSD; (3) low LA; and (4) low SLA due to thick and/or dense leaves, which contribute to long leaf survival, nutrient retention, and protection from desiccation and herbivory. Generalist plants had higher SLA than obligate serpentine plants, whereas the obligate serpentine plants showed more drought avoidance mechanisms than the generalists. Although most plant species inhabiting Mediterranean serpentine ecosystems have shown similar ecological adaptations in response to the Mediterranean environment, our results suggest that serpentine obligate plant species could present greater resilience to climate change. Given greater number and more pronounced drought avoidance mechanisms in these species compared with generalists, and the high number of FGs identified, the serpentine plants have shown adaptation to severe drought.